Difusi Inovasi Program Bus Suroboyo pada Masyarakat - Efa Rubawati Syaifuddin (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to see the diffusion of innovations carried out by the Surabaya City Government in the field of transportation through the Suroboyo Bus. The Suroboyo Bus innovation elicited various community responses as adopters which then grouped people according to their level of adoption. This qualitative descriptive research with case studies uses interviews and observation as data collection techniques. The results of this study found that there had been a diffusion of innovations carried out by the Surabaya City Government which made social media the main communication channel and mass media a supporting channel, so that the Suroboyo Bus innovation could be accepted by the people of Surabaya. The response of the religious community in responding to this innovation, some were very enthusiastic, some did not know about it until there were community groups who rejected the Suroboyo Bus innovation. This is influenced by several factors in the social system, one of which is the economy.